Δημιουργία Διαδικτυακού Τουριστικού Χάρτη για τη Ν. Τήνο - Μπεντίνι, Ελόνα (Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2017)
The scope of this master thesis is the creation of an interactive web mapping application for Tinos island. The content of the application and the purpose of the created map are part of the wider context of the promotion of the hiking network of the area of interest. The content visualization takes into account the current range of the user's devices. The map that is produced is based on the basic principles of visualization of web maps and mobile cartography. Furthermore, the system incorporates functional features that support the basic actions of mobile users that are relevant to space, such as location tracking, location searching and navigation. The softwares that were used to implement the above procedures are ArcGIS for Desktop 10.5 (ESRI) and QGIS 2.18, in order to collect, analyze and visualize the spatial data. Moreover, the Geoserver web server was used to publish the maps and spatial data from a variety of templates through the open interfaces such as WMS, WFS and Tile Caching. For the implementation of the system were also used the modern web development technologies, HTML5 / CSS3 / Javascript and the principles of Responsive Design. In addition, in order to build the web cartographic application the Leaflet open source Javascript Library has been used, which supports the development of interactive maps for mobile devices.